(643) Some Problems of Working and Utilization in Planning the Structural Balances (Input-Output Tables) in Czechoslovakia بعض مشاكل العمل والاستخدام في تخطيط التوازنات الهيكلية (جداول المدخلات والمخرجات) في تشيكوسلوفاكيا - Spevacek, Vojtech (INP, 2024)
paper